ATTITUDE AND MOTIVATION TOWARDS LEARNING ENGLISH AND KOREAN LANGUAGE OF THE KOREAN CULTURE ENTHUSIASTS IN SURABAYA - Firda Aprillia Rizmadana; Milal (ELite Journal : International Journal of Education, Language, and Literature, 2022)
This study aims to reveal the language attitudes of Korean culture enthusiasts in Surabaya and their motivations for learning English and the Korean language. It is in line with the increasing interest among the youth, especially in Surabaya, in learning foreign languages, together with the spread of the Korean wave. The data were collected by a questionnaire distributed to respondents who met the criteria of this study via WhatsApp, Instagram, and Twitter. Then, the data obtained were analyzed in different ways. To measure language attitudes, the data were analyzed using a five-point Likert scale. As for learning motivation, the data were analyzed by grouping respondents' answers into motivation categories. The results indicate that the attitude of Korean culture enthusiasts in Surabaya towards English and the Korean language seen from the three components of attitude is included in the "Good" category or can be interpreted as a positive attitude. The slight difference is that their attitude towards English is greater than that of the Koreans. The researchers also find four categories of motivation of the respondents: integrative, instrumental, intrinsic, and extrinsic.